KARAKTERISTIK FISIK, KIMIA, DAN ORGANOLEPTIK MIE MOSAF (MODIFIED SATOIMO FLOUR) (Colocasia esculenta) - Eliantosi -; Darius - (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Satoimo rich in Hyaluronic Acid ( HA ) , a substance produced naturally in the body and produce natural collagen . Taro flour relatively smooth and easy to digest useful for the preparation of pastries , cakes , breads and noodles . Noodle is one of the many products that are favored by all the community . Has conducted research aimed to analyze the characteristics of the physical, chemical and organoleptic noodles mosaf ( Colocasia esculenta ) . The treatment is done in this study is a comparison of wheat flour : flour mosaf with variations 450 g : 50 g ; 400 g : 100 g ; 350 g : 150 g ; 300 g : 200 g ; and 250 g : 250 g . The analysis in this study includes the analysis of the fiber content , elasticity and organoleptic ( color, taste, texture dam ) mosaf wet noodle . The results showed that the higher concentration mosaf flour is added , then the noodles fiber content becomes higher but getting lower elasticity , whereas the level of consumer preferences of the parameters of color, flavor and texture of getting down , the tolerance level of the composition of wheat flour : 400 g flour mosaf : 100 g .Keywords : noodles , satoimo , mosaf